PENERAPAN STATISTICAL QUALITY CONTROL DAN FAILURE MODE AND EFFECT ANALYSIS GUNA MENGURANGI KECACATAN PRODUK (STUDI KASUS: UMKM QUEEN PIE) - Muhammad Syarief Hidayatullah; Dzakiyah Widyaningrum; Akhmad Wasiur Rizki (Universitas Muhammadiyah Gresik, 2021)
Milk pie cake is the most popular product in MSME Queen Pie, but the number of orders is directly proportional to the resulting defect. Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA) methods are used to optimize this. In the study there are defects in milk pie cake is charred, immature, broken, bubbling and sticky. In the check sheet, the average defect per month is 8.6%. Furthermore, the flowchart in the production process consists of 3 parts, namely raw material handling, production and packaging. From the results of the Scatter Diagram shows that between production variables and defects are interconnected. Then on the histogram, the biggest defect is the rupture product with defect 844. In pareto seen dominant defect type rupture by 34.7%. Furthermore, the attribute map contains data out of control in February. The results of fishbone diagram analysis of the causes of defect factors are human, machine, method, material and environment. Based on the analysis of FMEA further improvement proposals are made that perform regular maintenance, give workers adequate rest periods, check the temperature of the oven periodically, more thorough in choosing flour with good quality and ensure the mold has been smeared with margarine before given the dough. Keywords : Quality Control, Defect, Failure Mode and Effect Analysis, Statistical Quality Control